PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA (Studi Kasus Desa Tolonuo, Kecamatan Tobelo Utara Kabupaten Halmahera Utara) - ibnu kanaha (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2018)
Community Participation in Rural Development is an obligation as stipulated in Law Number 6 Year 2014, article 63 paragraph (2) part (e) yakn "Participation in various activities in the village" is meant with various activities is village development activities.The form of this research is descriptive qualitative conducted in Donsa Tolonuo, North Tobelo Subdistrict, North Halmahera Regency. Data collection techniques are conducted by interviews, observations and other supporting documentation relevant to this research. Data examination techniques include degree of trust, dependency and certainty. Findings in research on Community Participation in Development (Tolonuo Village, North Tobelo Sub-district of North Halmahera District). Where village development can be designed to create more advanced and healthy socio-economic conditions for all communities through their active participation, and based on full confidence in their initiatives.Finally the researchers said Hopefully the results of this study, later, can provide benefits for the community, the world of academics and related apparatus.